Collective transcriptomic deregulation of hypertrophic and dilated cardiomyopathy – Importance of fibrotic mechanism in heart failure. (April 2018) - Malgija, Beutline; kumar, Nachimuthu Senthil; Piramanayagam, Shanmughavel
Graphical abstract: Highlights: Increased expression of Extracellular matrix proteins were observed in DCM and HCM. Alterations of collagen genes were observed. Up regulation of FMOD might competes the binding of LUM in DCM for a type I collagen COLA2. Analysis of submodules revealed the importance of SLRPs and collagens in heart failure. Both DCM and HCM follows different fibrotic pathway in progression of heart failure. Abstract: Myocardial fibrosis reside a common pathological feature in hypertrophic and dilated cardiomyopathy that results in ventricular dysfunction leading to heart failure. Though several studies reported the role of fibrosis in cardiac diseases, their pathologic mechanisms leading to heart failure remains unclear. A few studies have proposed integrated analysis of microarray information and protein–protein interaction (PPI) systems to discover subnetwork markers related to diagnosis and prognosis of the disease. In addition to PPI networks, we incorporated miRNAs and transcription factors to find the putative miRNAs and transcription factors that might regulate the pathological process and progression of cardiomyopathy and their further progression to heart failure. The important submodules from network revealed the significance of Small Leucine Rich Proteoglycans (SLRPs), Extracellular matrix (ECM) related proteins and complement system in fibrosis. Sequence analysis of different SLRPs suggest that Keratocan and Fibromodulin possesses the same collagen binding site. A predicted mechanism of TGFβ1 shows the involvement of different pathway of HCM and DCM in progression of heart failure.